Antioxidant activity of the ethanolic extracts of leaves, stems and fruits of Solanum nigrum - Nur Alam, Mohammad; Roy, Suvashish; Anisuzzaman, Sharif Mohammad; Rafiquzzaman, Mohammed (Pharmacognosy Communications)
Background: Solanum nigrum Linn. (Solanaceae) has been extensively used in traditional medicine in Bangladesh and other parts of the world to cure liver disorders, chronic skin ailments (psoriasis and ringworm), inflammatory conditions, painful periods, fevers, diarrhea, eye diseases etc. Materials and Methods: Crude ethanolic extracts of leaves, stems and fruits of Solanum nigrum were prepared and evaluated for antioxidant activity by two different in vitro methods. Results: All the prepared extracts have antioxidant potential. However, leaf extracts showed highest antioxidant activity irrespective of the method used. Gallic acid equivalent phenolic compounds content as well as quercetin equivalent flavonoids content were highest in the leaf extract of the S. nigrum and that could be the reason behind the highest antioxidant activity of leaf extract. Discussion: As leaf extract showed the highest antioxidant activity among all extracts, it might be investigated further for isolation of antioxidant principles.
Keywords: Solanum nigrum; DPPH; antioxidant activity; flavonoid content and phenolic compound content